Long term end‐stage renal disease and death following acute renal replacement therapy in the ICU. Issue 8 (24th May 2016) - Lohse, R.; Damholt, M. B.; Wiis, J.; Perner, A.; Lange, T.; Ibsen, M.
Abstract : Introduction: In ICU the need for acute renal replacement therapy (RRT) associates with high mortality and risk of end‐stage renal disease (ESRD), but there are limited long‐term data. We investigated these outcomes and their risk factors. Methods: Retrospective analysis of all adult patients admitted to a general, university hospital ICU 2005–2012, excluding chronic dialysis patients. ESRD was defined as need of RRT > 90 days or kidney transplant. Results: Of 5766 patients included, 1004 (16%) received acute RRT; their 30‐day mortality was 42% vs. 16% for those not requiring acute RRT (adjusted hazard ratio (HR) 1.13 (0.96–1.32)). The 90‐day mortality was 55% for patients receiving acute RRT vs. 22% for those who did not (adjusted HR 1.32 (1.15–1.51)) and 1‐year mortality was 63% vs. 30%, respectively, (adjusted HR 1.31 (1.16–1.48)). The 7‐year risk of ESRD for ICU patients surviving 90 days was 10% for patients who received acute RRT vs. 0.5% among those who did not (adjusted HR 5.9 (2.9–12.4)). Independent risk factors for ESRD included pre‐existing kidney disease, pre‐existing peripheral vascular disease and use of acute RRT in ICU. Conclusions: The need of acute RRT was associated with markedly increased long term risk of death and ESRD; in contrast its use was not associated with 30‐day mortality. In addition to acute RRT, decreased kidney function and peripheral vascular disease before ICU admission were risk factors for ESRD. It seems warranted offering medical follow‐up to patients after acute RRT in ICU.